Dynamic kinetic resolution of 2-methyl-2-nitrocyclohexanol: Combining the intramolecular nitroaldol (Henry) reaction & lipase-catalysed resolution. Issue 13 (29th March 2018) - Foley, Aoife M.; Gavin, Declan P.; Deasy, Rebecca E.; Milner, Sinéad E.; Moody, Thomas S.; Eccles, Kevin S.; Lawrence, Simon E.; Maguire, Anita R.
Abstract: Efforts to combine the intramolecular nitroaldol reaction with lipase-catalysed resolution of the resulting nitroaldol adduct in a one-pot dynamic kinetic resolution (DKR) are described. Significant challenges were encountered in the combination of the two systems. trans- 2-Methyl-2-nitrocyclohexyl acetate (±)-3b was isolated in excellent enantiopurity (>98% ee ) via a sequential DKR sequence where the lipase-mediated resolution and base-mediated interconversion of 2-methyl-2-nitrocyclohexanol2 were effected alternately, demonstrating the feasibility of this approach initially. Further work showed, for the first time, evidence that a DKR-type system is possible for2 . Reaction engineering allowed the design of a sequential one-pot reaction system which furnished the products with excellent enantioselectivity, and good diastereoselectivity. Graphical abstract: Herein, we describe the development of a reversible intramolecular base catalysed Henry reaction coupled with the hydrolase mediated kinetic resolution with the view to selective acetylation of a single stereoisomer is described.